A MIGHTY ONE: THE LEADERSHIP, SERVICE, AND LEGACY OF FRANCES HESSELBEIN - McArthur, Sarah (Leader to leader, 2023)
The author, the editor‐in‐chief of Leader to Leader, begins her tribute to Frances Hesselbein quoting from the 20th century writer George Bernard Shaw, including the following: Life is no “brief candle” for me. It is a sort of splendid torch which I have got hold of for the moment, and I want to make it burn as brightly as possible before handing it on to future generations.’’ She further discusses her close working relationship with Frances, and in describing the issue you are now reading, reflects that “She commanded the hearts and minds of the incredible mosaic of accomplished leaders and contributors who have assembled in this special commemorative issue of her beloved Leader to Leader journal. And we recognize that this is a mere drop in the bucket of the influence and impact of the mighty Frances Hesselbein.”